Teachers’ Strategic Use of Formative Assessment to Support Students With Learning Difficulties - Deljouei, Fariba; Bayat, Niloofar (Assessment and Practice in Educational Sciences, 2024)
This study aimed to explore how teachers strategically use formative assessment to support students with learning difficulties in inclusive classroom settings. This qualitative research employed a phenomenological approach to investigate the lived experiences of teachers implementing formative assessment practices. Data were collected through semi-structured interviews with 30 teachers from primary and secondary schools in Tehran, Iran. Participants were selected using purposive sampling, ensuring that all had direct experience working with students diagnosed with learning difficulties such as dyslexia, ADHD, and auditory processing disorders. Interviews were transcribed and thematically analyzed using Braun and Clarke’s six-phase framework, supported by NVivo software. Theoretical saturation was reached by the 30th interview. Three overarching themes were identified: differentiated assessment strategies, pedagogical responsiveness, and professional and contextual constraints. Teachers employed a range of adaptive techniques such as multimodal tools, scaffolded goal setting, and tiered tasks to accommodate learners’ needs. Pedagogical responsiveness included real-time instructional adjustments, emotional support, and culturally sensitive practices. However, systemic barriers—such as institutional pressure, lack of training, and emotional fatigue—limited the consistent application of formative assessment. Teachers emphasized the need for flexibility, emotional awareness, and studentcentered planning in their formative assessment approaches. The study reveals that while teachers possess the skills and commitment to strategically use formative assessment for students with learning difficulties, external constraints hinder full implementation. Effective formative assessment in inclusive classrooms requires pedagogical expertise, institutional support, and an assessment culture that prioritizes learning over standardization. Policy reforms and professional development are essential to enable teachers to assess responsively and equitably.